Validation of the Toronto Empathy Questionnaire (TEQ) Among Medical Students in China: Analyses Using Three Psychometric Methods - Xu, Richard Huan; Wong, Eliza Lai-yi; Lu, Sabrina Yu-jun; Zhou, Ling-ming; Chang, Jing-hui; Wang, Dong (Frontiers in Psychology, 2020)
This study aimed to validate the simplified Chinese version of the Toronto Empathy Questionnaire (cTEQ) for use with the Chinese population. The original English version of the TEQ was translated into simplified Chinese based on international criteria. Psychometric analyses were performed based on three psychometric methods: classical test theory (CTT), item response theory (IRT), and Rasch model theory (RMT). Differential item functioning analysis was adopted to check possible item bias caused by responses from different subgroups based on sex and ethnicity. A total of 1296 medical students successfully completed the TEQ through an online survey; 75.2% of respondents were female and the average age was 19 years old. Forty students completed the questionnaire two weeks later to assess the test-retest reliability of the questionnaire. Confirmatory factor analysis supported a 3-factor structure of the cTEQ. The CTT analyses confirmed that the cTEQ has sound psychometric properties. However, IRT and RMT analyses suggested some items might need further modifications and revisions.